The Influence of Work Environments on Human Resource Performance: The Mediating Role of Employee Retention - Kiatterdlar, Sucha; Ueasangkomsate, Pittawat (KKBS Journal of Business Administration and Accountancy, 2023)
The objectives of this research aimed to investigate the impact of work environments on human resource performance as well as the impact of work environments on human resource performance by the mediating role of employee retention. The questionnaire was used as a tool to collect data from 390 private employees from large firms in the food manufacturing and service. In this study, the statistics used were (1) descriptive statistics such as frequency, percentage, and standard deviation, and (2) inferential statistics including Pearson's correlation coefficient and regression analysis. The findings indicated that the influence of physical work environment and social work environment had a direct impact on human resource performance. Furthermore, it was shown that the influence of digital work environments had also impacted human resource performance by the mediating role of employee retention in the food manufacturing and service sectors. Hence, the results of the study provide a guideline for food organizations in developing human resource performance.